Combination of 177Lu-PSMA-617 and External Radiotherapy for the Treatment of Cerebral Metastases in Patients With Castration-Resistant Metastatic Prostate Cancer. (September 2017) - Wei, Xiao; Schlenkhoff, Carl; Schwarz, Bettina; Essler, Markus; Ahmadzadehfar, Hojjat
Abstract : Abstract: Two castration-resistant prostate cancer patients, both with cerebral and visceral and lymphatic metastases, received multiple cycles of 177 Lu-PSMA-617 treatments. The prognosis of both cases is dependent on brain metastases. Between 177 Lu-PSMA-617 treatment cycles, local radiotherapy was also applied to the brain metastases. Prior to the combined therapy, all systemic metastases, including cerebral lesions, showed PSMA expression using 68 Ga-PSMA PET/CT. Under the combined therapy, all the metastases, particularly the cerebral lesions, showed significant regression in size and PSMA expression over time.